Preposition Use on Students’ Writing Recount Text at Grade XI MAS Baharuddin - BatangAngkola– Tapanuli Selatan - zainuddin zainuddin (JURNAL LINER (Language Intelligence and Educational Research), 2021)
The research focuses on students’ preposition use on writing recount text. The problems of this research are students misuse preposition and confuse of using preposition in writing recount text. The reasons are students are lack of vocabulary, comprehension and preposition understanding in use on writing recount text. It is qualitative research which uses descriptive method. Source of data of this research is students of MAS Baharuddin - Batang Angkola - Tapanuli Selatan in class XI IPA, and there are 29 students. The instrument of this research is essay writing. Finally, the result of this research is students did the error on preposition use in writing recount text, were in omission, addition, misformation and misordering. The number of omission error was 7 items error. The number of addition error was 16 items error. The number of misformation error was 27 items error. The number of disordering error was 6 items error. Total all of the error were 56 item error. Researcher concluded that dominant error made by students in using preposition in writing recount text was in misformation category with the percentage 48, 2%. Key Words : Preposition, Writing, Recount Text